TICs em sala de aula: mediação para novas práticas de ensino e aprendizagem. - Salgado, Robnaldo Fidalgo (2016)
This work is based on the assumption that the school is one of the spaces for critical re-signification of the use of technology-mediated communication, by appropriating knowledge about the universe of digital culture and reflecting concepts in the classroom. The research investigated the challenges experienced by teachers of basic education in the use of Information and Communication Technologies (ICTs) in the classroom. The basis for the theoretical discussion was supported by authors from the fields of Philosophy, Education and Communication who have dedicated their research to the impacts of ICTs throughout society, including Castells, Lemos, Lévy, Martínez, Rada, Sacristán, Sancho and Tedesco. To answer the problem question: how do ICT contribute to mediation for new teaching and learning practices in the classroom ?, this research considered that, when thinking about education in the information society, it is necessary to reflect with teachers on aspects that Technologies, what their objectives are in relation to the training process. The objective of the research was to discuss the ICT space in the pedagogical practice of primary education teachers, who work in a public school in a city on the coast of the State of São Paulo, as well as to understand the challenges for pedagogical use of the tools in the classroom. class. In order to understand the complexity of the study, the methodological choice was based on a qualitative approach, with the data collection procedures being the focus group, observation, semi-structured interview and questionnaire. The results pointed out dilemmas and possibilities in the use of ICTs in teaching practice, which are real challenges for the effective incorporation of technological resources in the classroom. In relation to the challenges pointed out by the research participants, are: a) the need for ongoing training; B) lack of necessary infrastructure in relation to equipment and access to the Internet; C) difficulties in planning the use of equipment; D) difficulties to maintain authority before the student in the midst of the attractiveness of technological resources. Faced with the challenges cited by the teachers, possibilities arose for the use of technological resources in the classroom and for communication with parents and students, through technologies that allowed distance interactivity. The research data showed that the experiences of teachers and managers with the use of technological tools advance in teaching and learning practices, as the teacher has favorable conditions to explore more their potential for interaction and communication.